1323 Assessment of The Appropriate Use of Imaging and Reporting in Acute Pancreatitis in A Secondary Care Setting. (12th October 2021) - Kirchhoff, C; Omokehinde, T J; Achunine, P; Marshall, C; Ikechi, C; Shah, A
Abstract: Aim: Acute pancreatitis is the world's most common gastrointestinal disease requiring hospital admission. Our audit aim was to assess the timeframe within which Abdominal Ultrasound Scans (USS) and Computerised Tomography (CT) were performed, reported indications for CT and the prognostic factors noted in imaging reports. Method: A retrospective search included admissions with acute pancreatitis between 01/09/19 to 30/11/19, collecting demographics, admission time & date, time and date of both radiological investigations and imaging reports. Patients under the age of 18 were excluded. Results: This search identified 75 patients (M:F, 40:35) with a median age of 53 (18-95) years. USS were performed within 24 hours of admission in 40.0% (n = 30) of cases. Out of the patients (n = 44) who received a CT scan, 15.9% (n = 7) were scanned after more than 72 hours of onset of symptoms and 84.1% (n = 37) were scanned within less than 72 hours. Furthermore, 88.6%(n = 39) of CT request indications were in keeping with our standards. The average length of hospital stay was 6.1 days when scanned within 72 hours and 11.8 days when scanned after more than 72 hours. Conclusions: Only 17.3% (n = 13) of the patients audited met all our standards and were managed according to the guidelines. The average length of hospital stay was half in those who had a CT scan after more than 72 hours of admission and this was also used to monitor disease progression/regression.